THE EFFECT OF FISH WEIGHT ON FREEZING TIME - Hasanah Hasanah; Wulandari Wulandari; Afriani Afriani; M. Hariski; Lauura Hermala Yunita (Universitas Mataram, 2026)
Fish is a highly perishable fishery product because it contains approximately 70-80% water. Fresh fish was deterioration process qiuckly, so proper handling techniques are required, namely block freezing. Freezing is a decrease in the initial temperature to the freezing point. This study aims to determine the freezing time at different fish weights. The research method used is an experiment using 7 fish samples, namely banana fish, areca fish, wulan fish, pomfret fish, botan fish, tilapia, and catfish. The weight of each fish in this study was banana fish (22 g), areca fish (87 g), wulan fish (150 g), pomfret fish (85 g), botan fish (244 g), tilapia fish (247 g), and catfish (205 g). The freezing temperature experienced a rapid decrease in the 1st hour and began to slow down in the 2nd-3rd hour, remained at the 4th and 5th hours, then decreased again at the 6th hour and remained at the 7th and 8th hours, then the temperature decreased again at the 9th and 10th hours but remained at the 11th hour. At the 11th hour, the water surface in banana fish had frozen completely, pomfret, pinang, wulan, tilapia, catfish had not frozen completely, there were still small gaps, while botan fish had not frozen completely and there were still many gaps. The weight and species of the fish affect the freezing process.